High-risk patients with mild-moderate left ventricular dysfunction after a previous myocardial infarction. A long-term prognostic data by cardiac magnetic resonance. (15th October 2017) - Di Bella, Gianluca; Pizzino, Fausto; Aquaro, Giovanni Donato; Piaggi, Paolo; Venuti, Giuseppe; Carerj, Scipione; Pingitore, Alessandro
Abstract: Background: Few studies have explored prognosis in patients with previous myocardial infarction (MI) with mild-moderate (MM) left ventricular (LV) dysfunction (D). The aim of our study was to investigate whether combining LV parameters obtained by cardiac magnetic resonance (CMR) improves risk stratification of patients with previous MI and MM-LV-D. Methods: In 418 consecutive patients (63.3 ± 11.3 years old, female 12.9%) with previous MI, we quantified LVEF, volumes and wall motion score index (WMSI) and measured the infarct extent by late gadolinium enhancement (LGE). According to LVEF, patients were considered with normal LVEF (> 55%), MM-LV-D (LVEF > 30 and ≤ 55%) and severe (S) LV-D (LVEF ≤ 30). Results: During follow-up (median, 39.7 months) cardiac events (cardiac death or appropriate intra-cardiac defibrillator shocks) occurred in 17/99 of patients with S-LV-D, in 15/201 with MM-LV-D, and in only 1/118 of those with normal LV-EF. After adjustment for age, an extent of LGE > 11.3%, a dilated LV (male > 112 ml/m 2 ; female > 92 ml/m 2 ) and a WMSI > 1.59 were associated with adverse cardiac events in patients with MM-LV-D. In patients with MM-LV-D, when each of these 3 factors was observed, the prognosis was worse respect to those with 1–2 factors and no factor ( p = 0.035 and p = 0.004, respectively). Prognosis was similar ( p = 0.61) between MM-LV-D patients with all 3 factors and those with S-LV-dysfunction. CONCLUSIONS. A multiparametric CMR approach, which includes LGE, dilated LV and WMSI, permits to identify post MI patients with MM-LV-D with a risk of cardiac events similar to those with S-LV-D. Further multicenter studies are needed to confirm our data.